Mapping ecosystem services provided by benthic habitats in the European North Atlantic Ocean - Galparsoro, Ibon; Borja, Angel; Uyarra, María C. (Frontiers in Marine Science, 2014)
Mapping and assessing the ecosystem services provided by benthic habitats are a highly valuable source of information for understanding their current and potential benefits to society. The main objective of this investigation is to assess and map the ecosystem services provided by benthic habitats of the European North Atlantic Ocean, in the context of “Mapping and Assessment of Ecosystems and their Services” (MAES) programme, the European Biodiversity Strategy and the implementation of the Marine Strategy Framework Directive. In total, 62 habitats have been analysed in relation to 12 ecosystem services over 1.7 million km2. Results indicated that more than 90% of the mapped area provides biodiversity maintenance and food provision services; meanwhile grounds providing reproduction and nursery services are limited to half of the mapped area. Benthic habitats generally provide more services closer to shore than offshore and in shallower waters. This gradient is likely to be explained by difficult access (i.e. distance and depth) and lack of scientific knowledge for most of the services provided by distant benthic habitats. This research has provided a first assessment of the benthic ecosystem services at Atlantic European scale, with the provision of ecosystem services maps and their general spatial distribution patterns. Related to the objectives of this research, the conclusions are: (i) benthic habitats provide a diverse set of ecosystem services, being the food provision and biodiversity maintenance services the ones that are more extensively represented. In addition, other regulating and cultural services are provided in a more limited area; and (ii) the ecosystem services assessment categories are significantly related to the distance to the coast and with depth (higher near the coast and in shallow waters).